Solubility of CO2 in Brine and Reservoir Oil for Depleted Reservoirs in China - Zhang, Ke; Ma, Desheng; Li, Shi; Chen, Xinglong (Journal of Applied Solution Chemistry and Modeling, 2014)
Many countries play an important role to carbon capture, utilization, and Storage (CCUS) to reduce emission. Geological storage is an important approach to cope with climate change. Live oil combined with saline aquifers and gas reservoirs are among the candidates for carbon dioxide (CO2) sequestration, owing to their proven sealing capabilities and characterization. CO2 mainly from power industrial was captured to improve oil recovery in some oilfields in China, and solubility is a key factor to evaluate storage ability of reservoir and saline aquifer. In this paper, CO2 sequestration mechanisms in deplete reservoir and saline aquifer were explained. An experimental method to test solubility of CO2 in emulsion system of liver oil and brine was developed. The experimental results showed that with the salinity increased, the solubility of CO2 in reservoir oil increased slightly, and the solubility of CO2 in brine decreased. Salinity has little impact on solubility of CO2 in reservoir oil. With the pressure increased, the solubility of CO2 in reservoir oil and brine both increased. Molecular diameter of reservoir oil and white oil have inverse proportion relationship with the solubility Research on solubility of CO2 in brine and reservoir oil for depleted reservoir in China enabled us to better predict and deal with the challenges for rapid development of carbon storage.